Elevation in Peripheral Blood Circulating Tumor Cell Number Correlates with Macroscopic Progression in UICC Stage IV Colorectal Cancer Patients. Issue 3 (2008) - Molnar, Bela; Floro, Lajos; Sipos, Ferenc; Toth, Bernadett; Sreter, Lydia; Tulassay, Zsolt
Abstract : Aims: Cytokeratin(CK) based real-time RT-PCR assays (QRT-PCR) are now available for peripheral blood circulating tumor cell (CTC) evaluations in colorectal cancer(CRC) patients. Results are non-existent for the application of these techniques to the determination of progression and therapy response in Dukes stage D CRC patients. Patients and methods: Each month 30 ml peripheral blood of 30 Dukes D patients (17 with progression) were drawn. CEA, CA19-9, CA72-A and TPA-M determinations were made. CK20, thymidilate synthase(TS) QRT-PCR was performed, as well. Buffy coat was used for immunmagnetic cancer cell isolation and CTC counting. Correlation between elevated CTC and macroscopic progression within 3 months was determined by Chi 2 test. Results: Microscopic CTC single cell, doublet, cluster number were found in correlation with CK20 QRT-PCR results ( p < 0.01). There was a significant increase in microscopic CTC number, CK20 and decrease in TS QRT-PCR levels ( p < 0.05) in the peripheral blood of the non-responder as compared to responder patients. Elevation of the CTC was in significant correlation with macroscopic progression of the disease in 3 months ( p < 0.01). Conclusions: CTC number reflects the chemotherapeutic sensitivity of CRC patients. Elevation of circulating tumor cell number in peripheral blood is in correlation with macroscopic progression.